Pola Kalimat Opini Gubernur dalam JawaPos untuk Komunikasikan Hari Guru Nasional - Kasmanah; Miftahulkhairah Anwar; Saifur Rohman (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research highlights the crucial role of governors as regional leaders in conveying messages and policies to the community, especially through opinions published in the mass media. The focus on the use of formal and informal language in the governor's communication, as well as the analysis of sentence patterns in the opinion of the Governor of East Java in the November 25, 2023 edition of Jawa Pos are the main objectives of this study. Content analysis methods are used to evaluate opinion texts, examine sentence types, sentence patterns, and formal and informal language usage. The results showed the dominance of the use of active voice in the governor's opinion, indicating awareness of the subject as the main actor in the message conveyed. Common sentence patterns such as KSPO and SPK are often used, but there are also variations of other patterns that provide a broader dimension in communication. There is also a unique blend of formal and informal language in the governor's text, creating a more personal atmosphere and connecting with the audience more thoroughly. However, the study has limitations, especially in the overall representation of the governor's communication style that may not include all communication strategies in different situations. In conclusion, the study reveals complexity and variation in language use and sentence patterns in governors' opinions.